Embedded Function Composition - Whitted, Turner; Kajiya, Jim; Ruf, Erik; Bittner, Ray (Proceedings of the Conference on High Performance Graphics 2009, 2009)
A low-level graphics processor is assembled from a collection of hardwired functions of screen coordinates embedded directly in the display. Configuration of these functions is controlled by a buffer containing parameters delivered to the processor on-the-fly during display scan. The processor is modular and scalable in keeping with the demands of large, high resolution displays.